اقبالیات کی گم شدہ کڑی: The Missing link of Iqbaliat - احمد ڈاکٹر گل (Tashkeel e Jadeed, 2024)
New antiquities in Iqbal Studies are unveiled from time to time. This article also contains two antiquities. These antiquities consist of correspondence between Dr. Rahim Bakhsh Shaheen and Dr. Barfield. In this article, the text and text of these letters are explained. Moreover, necessary footnotes have been added for explanation, which will prove to be a new addition to the subject of Iqbal Studies.Dr. Rahim Bakhsh Shaheen is a well-known Iqbal scholar, while Dr. Barfield is the grandson of Allama Iqbal's teacher, Sir Thomas Arnold. Iqbal's relationship with the Arnold family was very devoted and he corresponded with them. This article discusses the nature of this relationship and Iqbalati unveils new additions to literature.